Comparison of the Siesmic Performance of the Patra Hotel Building in Surabaya with a Dilatation System Using Pushover Analysis - Achmad Fadli Erlangga; Wahyu Kartini; Sumaidi Sumaidi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The Patra Hotel Surabaya features an irregular L-shaped plan, making it highly susceptible to torsional irregularities in the seismically active region of Surabaya. This study aims to design an expansion joint (dilatation) system, determine the location of structural separation, select appropriate joint materials, and analyze the seismic performance of the structure in both conditions: without and with dilatation. The model without dilatation treats the original L-shaped building as a single structure. In contrast, the dilatation model separates it into two blocks: Model 1 represents the first block and Model 2 the second. The seismic response was evaluated using a performance-oriented design method that employed pushover analysis in accordance with ATC-40 and SNI 1726:2019. The findings indicate that Model 1 experiences a peak displacement of 88.209 mm in the X-axis and 73.431 mm in the Y-axis, while Model 2 reaches a maximum displacement of 71.841 mm in the X-axis and 85.047 mm in the Y-axis. Based on these results, the required expansion joint gap (?mt) is 150 mm. The expansion joint uses aluminium material with a movement capacity of ±75 mm for thermal effects and ±150 mm for seismic effects, exhibiting flexible, elastic behaviour. The pushover analysis results demonstrate that both Model 1 and Model 2 reached the Immediate Occupancy performance, with ductility figures of 9.89 for the X-axis and 7.65 for the Y-axis for Model 1, and 9.59 for the X-axis and 7.94 for the Y-axis for Model 2. A comparison of their seismic performance reveals that the model lacking dilation exhibited a greater maximum deviation, measuring 173.404 mm in the X-axis and 145.164 mm in the Y-axis. In comparison, Model 1 has 172.933 mm (X) and 141.229 mm (Y), while Model 2 has 137.923 mm (X) and 165.639 mm (Y). The drift ratio of the model without dilatation is also higher, at 1.149 (X) and 1.116 (Y), compared to Model 1 (1.087 (X) and 1.073 (Y)) and Model 2 (1.020 (X) and 1.104 (Y). Furthermore, the column reinforcement requirements in the model without dilatation are greater (K1 32D22, K2 28D22, K3 24D22) compared to the dilatation system (K1 28D22, K2 24D22, K3 20D22). Therefore, the implementation of a dilatation system is proven to improve seismic performance by reducing maximum displacement and drift ratio, while also resulting in a safer and more economical structural design. Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality Education; SDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and Communities